2016
DOI: 10.1139/cjss-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and species richness of mycorrhizal fungi in soil under different land use

Abstract: This study aimed to assess the impact of different land uses on the spore density and richness of arbuscular mycorrhizal fungi (AMF) in a Red Latosol of a tropical savanna biome in Brazil ("Cerrado"). Ten soil samples and roots were obtained from a riparian forest, a pasture, an annual crop production system with no tillage, and a coffee plantation in dry and wet seasons. Spores were extracted, counted, and identified from field soils, and roots were stained to assess mycorrhizal colonization. A total of 42 AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 36 publications
(35 reference statements)
2
11
1
Order By: Relevance
“…This density may have been influenced by collection at the end of the dry period in Brazil, since water deficit can stimulate sporulation of AMF species (Ferreira;Saggin, 2012). In particular for the CE environment, the spore density found in this study was similar to that found by Fernandes et al (2016) in Riparian forest in the Cerrado environment.…”
Section: Resultssupporting
confidence: 72%
“…This density may have been influenced by collection at the end of the dry period in Brazil, since water deficit can stimulate sporulation of AMF species (Ferreira;Saggin, 2012). In particular for the CE environment, the spore density found in this study was similar to that found by Fernandes et al (2016) in Riparian forest in the Cerrado environment.…”
Section: Resultssupporting
confidence: 72%
“…Our findings confirm that in humid tropical areas the AMF spore species (Aidar et al, ; Picone, ; Zangaro et al, ) and mycorrhized roots (Muthukumar et al, ; Siqueira & Saggin‐Júnior, ; Treseder & Cross, ) tend to be associated with vegetation type and soil fertility as has been found in other studies performed in the tropics. Undoubtedly, this scenario displayed by the spores could not be the same as the colonized roots, which could harbor not sporulated species; however, the morphological approach brings valid and quick results about the communities of AMF (Fernandes et al, ; Landis, Gargas, & Givnish, ).…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi inventories in coffee-growing areas of southeastern Brazil, Colombia and Venezuela showed widespread occurrence of species of the genus Acaulospora, followed by Glomus (Saggin Júnior and Siqueira 1996;Cogo et al 2017). Species of the genus Glomus and Acaulospora (Arias et al 2012;Fernandes et al 2016) are usually predominant in coffee plantations; thus, dominance of species of the genus Gigaspora in coffee fields has not been frequently reported. In a previous study conducted in a greenhouse, the species Gigaspora margarita was found to be one of the most efficient in promoting growth and nutrition of coffee trees (Saggin Júnior and Siqueira 1996).…”
Section: Resultsmentioning
confidence: 99%